Modeling of trawl doors with account of the currents - Victor V. Chernetsov (Известия ТИНРО, 2016)
Mathematical model of trawl doors is presented and methods of their modeling with account of the water currents are described. The model could be used for optimal tooling of trawl systems for real environments.